Sistem Informasi Koperasi Simpan Pinjam Pada PT Meiwa Indonesia Berbasis Java - Nurrohman Nurrohman; Rudi Apriyadi Raharjo; Anggun Citra Dini Dwi Puspitasari (Innovation in Research of Informatics (INNOVATICS), 2020)
The purpose of this research is to make a Java-based savings and loan cooperative information system design to accelerate and facilitate performance in managing the search and storage of loan data at cooperatives as well as to produce a Java-based savings and credit cooperative information system. The research method used by researchers is the grounded research method, which is a research method based on facts and uses comparative analysis with the aim of conducting empirical generation, establishing concepts, proving theories, developing theories, collecting data and analyzing data in the same time. The results obtained are designing a savings and loan cooperative information system to assist in processing employee data. The construction of this information system is expected to simplify and provide maximum service for employees as well as to facilitate cooperative staff in collecting loan transaction data for reporting, data and information management processes become more effective, produce faster outputs and there is no misappropriation of loan data input or the occurrence of data duplication.